Association study of 5-HT1A, 5-HT2A polymorphisms with schizophrenia and major depressive disorder in the Han Chinese population. (2nd December 2016) - Zhang, Rui; Bi, Yan; Niu, Weibo; Huang, Xiaoye; Chen, Shiqing; Li, Xingwang; Wu, Xi; Cao, Yanfei; Yang, Fengping; Wang, Lu; Li, Weidong; Xu, Yifeng; et al.
Highlights: We investigated the association of 5-HT1A and 5-HT2A polymorphisms with both schizophrenia and major depressive disorder. The rs10042486 in 5-HT1A demonstrated significant difference between schizophrenia patients and controls. The 5-HT1A might be associated with schizophrenia in Chinese Han population. The rs1364043 and rs17289304 involved in our association study were explored for the first time. Abstract: Schizophrenia (SZ) and major depressive disorder (MDD) are two common severe mental disorders that have arisen to public awareness in recent years. Serotonin (5-HT) receptors have been implicated in the pathophysiology of psychiatric disorders especially in MDD and SZ. The aim of this study is to explore whether the variants in the 5-HT1A and 5-HT2A gene are susceptible to SZ or MDD in the Chinese Han population. Five SNPs (Single Nucleotide Polymorphisms) (rs1364043, rs10042486, rs6313, rs6311, rs17289304) in these genes were genotyped from 752 SZ patients, 568 MDD patients, and 846 normal controls of Chinese Han origin. The results showed that the 5-HT1A rs10042486 was significantly associated with SZ ( P allele  = 0.0369, P genotype  = 0.0098). Moreover, the haplotype (C-T) composed of rs10042486 and rs1364043 showed significant difference between SZ cases and healthy controls ( P  = 0.0302) while another haplotype (T-G) was significant for MDD ( P  = 0.0247). Our study is the first to suggest a positive association of the 5-HT1A gene with SZ in the Han Chinese population.